2019
DOI: 10.1101/761759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sumoylation is largely dispensable for normal growth but facilitates heat tolerance in yeast

Abstract: Sumoylation is an essential, conserved protein modification with hundreds of targets. Compared to the related modification ubiquitination, few enzymes are involved in SUMO conjugation and deconjugation, including a single conjugase, Ubc9, in yeast and mammals. This suggests that cells can simultaneously control the sumoylation level of numerous proteins by regulating just one enzyme of the SUMO pathway. Such modulated levels of cellular sumoylation are observed in response to a number of stress conditions, whi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(177 reference statements)
0
2
0
Order By: Relevance
“…As shown in Fig 1A , the vast majority of sumoylated proteins in both organisms are chromatin-bound, supporting the notion that SUMO functions primarily in regulating processes associated with chromatin, such as gene regulation. To examine specifically where sumoylated proteins are stably bound to the yeast genome, we carried out a ChIP-seq experiment using a genetically unmodified, normally growing strain (W303a) and an antibody that is specific for yeast SUMO [ 45 ]. Stringent analysis of two independent SUMO ChIP-seq replicates identified a common set of 603 robust SUMO peaks across the yeast genome ( S1A Fig and S2 , S4 and S9 Tables).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig 1A , the vast majority of sumoylated proteins in both organisms are chromatin-bound, supporting the notion that SUMO functions primarily in regulating processes associated with chromatin, such as gene regulation. To examine specifically where sumoylated proteins are stably bound to the yeast genome, we carried out a ChIP-seq experiment using a genetically unmodified, normally growing strain (W303a) and an antibody that is specific for yeast SUMO [ 45 ]. Stringent analysis of two independent SUMO ChIP-seq replicates identified a common set of 603 robust SUMO peaks across the yeast genome ( S1A Fig and S2 , S4 and S9 Tables).…”
Section: Resultsmentioning
confidence: 99%
“…The difficulty in detecting SUMO at non-RPGs promoters may be related to the highly labile nature of the modification [ 45 ]. In support of this, we found that partially inactivating the SUMO protease Ulp1 resulted in increased sumoylation of chromatin-associated Tfg1, suggesting that the protein is normally subject to some level of desumoylation.…”
Section: Discussionmentioning
confidence: 99%